ANALISIS TINDAKAN PENGHINDARAN PAJAK PADA PERUSAHAAN YANG MEMPUNYAI KONEKSI POLITIK (STUDI PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013) - PUJI HARDIANTI, EKA Puji (Jurnal Akuntansi AKUNESA, 2014)
This study aims to describe so many higher phase of tax avoidance that doing by companies which has political connections by using descriptive quantitative research. The data type that used is the secondary data. Population in this study is BUMN listed on the Indonesia stock exchange in 2010 until 2013. The result showed that a lot of BUMN doing of tax avoidance. Increasingly higher phase of political connections that has companies so increasingly higher preference of tax avoidance. From 10 BUMN as sample there are only 2 BUMN that not doing of tax avoidance from 2010 until 2013. The balance is ever doing tax avoidance.Keyword : political connections, tax avoidance and BUMN